Pericardial involvement by thymomas: entirely intrapericardial thymoma and a pericardial metastasis of thymoma with glomeruloid vascular proliferations - Bläker, Hendrik; Otto, Herwart F. (Pathology & oncology research, 2002)
Thymomas are usually found in the anterior mediastinum, the normal location of the thymus. Involvement of the pericardium by thymic tumors is seen in invasive or metastasized thymoma. Very rarely, thymomas arise primarily in the pericardium. These tumors are believed to derive from thymic tissue which was misplaced in the pericardium during embryologic development. In contrast to patients with orthotopic thymoma who commonly suffer from paraneoplastic diseases, especially myasthenia gravis, patients with intrapericardial thymoma manifestations mainly have symptoms of congestive heart failure which are caused by local complications of tumor growth. In this study, we present two cases of thymoma involving the pericardium. Both tumors were polygonal-oval cell thymomas. In one of the cases diagnosis of an entirely intrapericardial thymoma was established by autopsy. In the other case, explorative thoracotomy revealed massive pericardial and pleural tumor manifestations. The latter tumor showed a peculiar histological pattern with multiple glomeruloid bodies, a finding reported only once for thymomas. Copyright 1999 W.B. Saunders Company Ltd on behalf of the Arányi Lajos Foundation